2021
DOI: 10.1002/advs.202102568
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Type III Adenylyl Cyclase in the VMH Is Crucial for High‐Fat Diet‐Induced Obesity Mediated by Autophagy

Abstract: Neuronal primary cilia are crucial for body weight maintenance. Type III adenylyl cyclase (AC3) is abundantly enriched in neuronal cilia, and mice with global AC3 ablation are obese. However, whether AC3 regulates body weight through its ciliary expression and the mechanism underlying this potential regulation are not clear. In this study, humanized AC3 knock‐in mice that are resistant to high‐fat diet (HFD)‐induced obesity are generated, and increases in the number and length of cilia in the ventromedial hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Consequently, the disruption of cilia genesis or cilia-based signaling causes a set of overlapping human disorders, including sensory defects, obesity, infertility, cystic kidney disease, developmental abnormalities, intellectual disability, and mental disorders, which are collectively termed ciliopathies ( Anvarian et al., 2019 ; Reiter and Leroux, 2017 ). Because AC3 is almost exclusively concentrated in the cilia of diverse neuron types in the brain ( Bishop et al., 2007 ; Sipos et al., 2018 ), our current results coupled with those from previous studies demonstrate that the ablation of AC3 in mice also leads to pleiotropic phenotypes, including anosmia, cognitive deficit, obesity, and depression-like behaviors, in a brain region-specific and cell type-specific manner ( Challis et al., 2015 ; Chen et al., 2016 ; Chesler et al., 2007 ; Col et al., 2007 ; Guadiana et al., 2013 ; Liu et al., 2020a , 2020b ; Livera et al., 2005 ; Siljee et al., 2018 ; Wang et al., 2006 , 2009 , 2011 ; Wang and Storm, 2011 ; Yang et al., 2021 , 2022 ; Zhang et al., 2017 ; Zhou et al., 2021 ; Zou et al., 2007 ). Intriguingly, a recent study showed that neuropilin 2 (Nrp2), an axon guidance molecule, plays crucial roles in instructing circuit formation from the MOB to MeA for the transmission of attractive social signals in the brain ( Inokuchi et al., 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, the disruption of cilia genesis or cilia-based signaling causes a set of overlapping human disorders, including sensory defects, obesity, infertility, cystic kidney disease, developmental abnormalities, intellectual disability, and mental disorders, which are collectively termed ciliopathies ( Anvarian et al., 2019 ; Reiter and Leroux, 2017 ). Because AC3 is almost exclusively concentrated in the cilia of diverse neuron types in the brain ( Bishop et al., 2007 ; Sipos et al., 2018 ), our current results coupled with those from previous studies demonstrate that the ablation of AC3 in mice also leads to pleiotropic phenotypes, including anosmia, cognitive deficit, obesity, and depression-like behaviors, in a brain region-specific and cell type-specific manner ( Challis et al., 2015 ; Chen et al., 2016 ; Chesler et al., 2007 ; Col et al., 2007 ; Guadiana et al., 2013 ; Liu et al., 2020a , 2020b ; Livera et al., 2005 ; Siljee et al., 2018 ; Wang et al., 2006 , 2009 , 2011 ; Wang and Storm, 2011 ; Yang et al., 2021 , 2022 ; Zhang et al., 2017 ; Zhou et al., 2021 ; Zou et al., 2007 ). Intriguingly, a recent study showed that neuropilin 2 (Nrp2), an axon guidance molecule, plays crucial roles in instructing circuit formation from the MOB to MeA for the transmission of attractive social signals in the brain ( Inokuchi et al., 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…An Adcy3 knockdown in the VMH using Cre-recombinase methods produced hyperphagia-associated obesity in mice on a standard diet ( Cao et al, 2016 ). In a separate study, ciliary ADCY3 knockdown in the VMH using CRISPR-Cas9 did not induce significant weight gain on a standard diet but did result in increased susceptibility to a high-fat diet in mice ( Yang et al, 2022 ). Altered autophagy due to a deficiency of ciliary ADCY3 may contribute to the development of obesity.…”
Section: Primary Cilia Integrate Peripheral Signals At Hypothalamic C...mentioning
confidence: 99%
“…Furthermore, when ADCY3 deletion is specific to the ventromedial hypothalamus (VMH), weight gain is pronounced in animals on a high fat diet (HFD). In addition, ADCY3 regulates autophagy by binding to gamma-aminobutyric acid A receptor-associated protein (GABARAP) ( Yang et al, 2022a ). Interestingly, autophagy is another mechanism thought to be used by cilia to regulate signaling ( Pampliega et al, 2013 ; Orhon et al, 2015 ), and there is growing evidence to support a bi-directional relationship between ciliogenesis and autophagy ( Ávalos et al, 2017 ).…”
Section: Genetic Mouse Models Of Cilia Associated Obesitymentioning
confidence: 99%
“…In ADCY3 knockout mice, there is a reduction of p62 and an increase in LC3-II, two proteins that regulate autophagy ( Cao et al, 2016 ). Similarly, an increase in LC3-II and decrease in p62 is observed when overexpression of ADCY3 is inhibited using an AVV carrying constitutively active GPR88, a Gi- protein coupled receptor (( Siljee et al, 2018 ); ( Yang et al, 2022a )).…”
Section: Genetic Mouse Models Of Cilia Associated Obesitymentioning
confidence: 99%